Pengaruh Waktu Penyelesaian Disbursement terhadap Kegiatan Operasional Head Office PT. Adhika Samudera Jaya pada Tahun 2022 - Dwinita Nuraisyah Saputri; Intan Sianturi; Femmy Asdiana; Rizqi Aini Rakhman (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
The aim of this research is to examine the influence of disbursement completion time on operational activities. Disbursement is the process of channeling funds by a company to third parties. Operational activities are actions carried out by the company's administrative center, such as planning, coordinating and supervising operations in various branches. The research method used is quantitative by collecting data through questionnaires given to company staff. The collected data was analyzed using simple linear regression to assess the influence of the independent variable (disbursement completion time) on the dependent variable (operational activities) involving 30 respondents. The data processing tool in this research uses SPSS for Windows ver. 25. The study results show that disbursement completion time has a significant influence on operational activities at the company's head office, with a coefficient of determination (R Square) reaching 78%. This means that the completion of disbursement time has an influence of 78% on the course of operational activities.